2013
DOI: 10.7213/academica.10.s01.ao17
|View full text |Cite
|
Sign up to set email alerts
|

DINÂMICA ENTRE TEMPERATURAS DO AR E DO SOLO SOB DUAS CONDIÇÕES DE COBERTURA Dynamic between air and soil temperature under two conditions of coverage

Abstract: Variações na temperatura do solo podem afetar significativamente a interação solo-planta. A aplicação de cobertura vegetal morta sobre o solo tem sido utilizada para protegê-lo contra variações bruscas de temperatura, reduzir a perda de água, etc., e assim modificando o microclima específico e vários processos físicos, químicos e biológicos. Neste estudo, avaliou-se a variação da temperatura no perfil do solo em condições de solo descoberto e com cobertura de palha seca, verificando a correlação entre a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
2
4
0
3
Order By: Relevance
“…Therefore, the 0.10 m layer for all months showed a soil temperature fluctuation closer to the 0.05 m layer than to the 0.20 m layer. Similar results were found by Belan et al (2013) and Diniz et al (2014), who found that maximum temperatures occurred at different times. The delay from surface to deeper depths showed that the heat wave requires a certain time period to propagate in the soil because of slow heat conduction capacity through the vertical soil profile, as mentioned above.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221supporting
confidence: 79%
See 3 more Smart Citations
“…Therefore, the 0.10 m layer for all months showed a soil temperature fluctuation closer to the 0.05 m layer than to the 0.20 m layer. Similar results were found by Belan et al (2013) and Diniz et al (2014), who found that maximum temperatures occurred at different times. The delay from surface to deeper depths showed that the heat wave requires a certain time period to propagate in the soil because of slow heat conduction capacity through the vertical soil profile, as mentioned above.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221supporting
confidence: 79%
“…In the same soil and location, Oliveira et al (2010) found regions closer to the soil surface showed lowest temperatures around 5 a.m. and maximum temperatures around 2 p.m. In a Latossolo Vermelho-Amarelo in the state of Espírito Santo, Brazil, Belan et al (2013) also found maximum values in the surface layer between 12 noon and 2 p.m., and Kunz et al (2002) found that the maximum soil temperature occurred around 4 p.m., which corroborates the results of this study.…”
Section: Rev Bras Cienc Solo 2018;42:e0170221mentioning
confidence: 99%
See 2 more Smart Citations
“…Com relação à característica número de plantas por hectare, todas as coberturas apresentaram resultado superior ao do sistema convencional. Isso pode ser explicado devido alguns fatores benéficos do SPD para o solo, como, maior umidade, menor variação de temperatura, melhor absorção de água, e proteção contra erosões entre outros fatores assim como relataram os autores Belan et al (2017) e Falci Dechen et al (2015, o que favoreceu o desenvolvimento e a manutenção do maior número de plantas por unidade de área nos sistemas com uso de plantas de cobertura. Mesmo com uma menor média de plantas por hectare, as médias de produtividade da soja sobre sistema convencional foi de aproximadamente 72 sacas ha -1 .…”
Section: Resultsunclassified